VISUAL DICTIONARY FOR LEARNING VOCABULARY FOR YOUNG ENGLISH LEARNERS - Somba, Sugianti; Widyaningrum, Winda (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
One of the main problems in English learning for beginner learners is vocabulary acquisition. The ability to communicate and understand a language is often hampered by a limited vocabulary. Visual dictionaries, which display the meaning of learnt words through pictures, are a method that can accelerate vocabulary comprehension. This method is considered more efficient because the human brain more easily remembers information that is accompanied by images or visuals rather than just text. The purpose of this study is to find out how effective the use of visual dictionaries is in learning vocabulary for beginner learners. By analysing the results and pedagogical methods used, the researcher examined how visual dictionary representation can increase students' interest and success in vocabulary acquisition as well as improve word recognition, comprehension and retention. This study utilised the classroom action research method. The research findings showed pre-test data that 77% of students were able to understand the vocabulary and 67% of students were able to pronounce the vocabulary correctly. Overall, the students' vocabulary mastery ability during the pre-test was 72%. Post-test data showed that 80% of students were able to understand the vocabulary and 83% of students were able to pronounce the vocabulary correctly. Overall, the students' vocabulary mastery ability during the post-test was 81.5%. Based on the above facts, the researcher concluded that visual dictionaries can improve the vocabulary acquisition of beginner learners.